Rancangan Pengendalian Internal Manajemen Risiko ISO 31000 Pengadaan Barang Jasa Badan Bahasa - Rania Az Zahra; Michael Musyaffi, Ayatulloh; Nasution, Hafifah (LPPM Universitas Negeri Jakarta, 2025)
This study aims to design an internal control framework through risk management based on ISO 31000 in the procurement of goods and services at the Badan Pengembangan dan Pembinaan Bahasa. The research addresses the issues of ineffective internal control implementation and inadequate risk mitigation within the procurement process, with variables including internal control, risk management, and procurement of goods and services. A qualitative research method with a case study approach was employed, using purposive sampling to select three informants from relevant procurement and financial units. Data were collected through interviews, documentation, and observation. The findings reveal several weaknesses in risk assessment and control activities, particularly regarding inaccurate needs assessment, unclear technical specifications, and disturbances in the SPSE system. The study proposes an integrated internal control design based on the COSO framework, enhanced with ISO 31000 risk management principles to improve efficiency, accountability, and risk mitigation in procurement processes.